2012
DOI: 10.1177/0163443712455558
|View full text |Cite
|
Sign up to set email alerts
|

Removing Justitia’s blindfold: the mediatization of law in Israel

Abstract: This article analyzes the process of mediatization in the legal sphere in Israel. It maps the reciprocal relations between legal professionals and journalists in Israel, and examines the impact of the changes that have occurred in the media on the press coverage of the courts, on legal decision-making and on the legal process. Interviews with judges, lawyers and journalists reveal that, despite evidence of the mediatization of the legal sphere, a number of factors serve to contain this process. We suggest the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…Our results showed that, all of the 13 articles that carried out any primary empirical work on the concept discussed change over time, but the majority (7) demonstrated a 'synchronous' research strategy (Hepp, 2013: 624), that is, their research focused on a single time period (Fortunati, 2005;Jansson, 2002;Kunelius and Reunanen, 2012;Peleg, and Bogoch, 2012;Schrøder, and Phillips, 2007;Strömbäck and Dimitrova, 2011;van Aelst, et al, 2008). Of the remainder that attempted a 'diachronous' strategy (ibid.…”
Section: Comparisons Over Time and Space?mentioning
confidence: 74%
See 1 more Smart Citation
“…Our results showed that, all of the 13 articles that carried out any primary empirical work on the concept discussed change over time, but the majority (7) demonstrated a 'synchronous' research strategy (Hepp, 2013: 624), that is, their research focused on a single time period (Fortunati, 2005;Jansson, 2002;Kunelius and Reunanen, 2012;Peleg, and Bogoch, 2012;Schrøder, and Phillips, 2007;Strömbäck and Dimitrova, 2011;van Aelst, et al, 2008). Of the remainder that attempted a 'diachronous' strategy (ibid.…”
Section: Comparisons Over Time and Space?mentioning
confidence: 74%
“…Where articles presented theoretical discussion and/ or primary empirical research, the majority inclined towards the social constructivist rather than institutionalist approach (10 to 3) (Elmelund-Praestekaer et al, 2011;Fortunati, 2005;Jansson, 2002;Kepplinger, 2002;Kunelius and Reunanen, 2012;Peleg and Bogoch, 2012;Reich, 2005;Schrøder, and Phillips, 2007;Schulz et al, 2005; 2011a. compared to Hopmann and Strömbäck, 2010;Strömbäck and Dimitrova, 2011;van Aelst, et al, 2008).…”
Section: Contemplating Causal Processesmentioning
confidence: 99%
“…As part of the review, we also looked for use of temporal concepts in these studies. One that received some attention was mediatization, which was typically used to describe media-related change (see Kepplinger, 2002;Peleg & Bogoch, 2012). Many other relevant temporal concepts, such as duration, pace, trajectory, and cycles (see Aminzade, 1992), were not used in any of the studies.…”
Section: Trend Mappingmentioning
confidence: 99%
“…This is what the concept of 'mediatization', which has recently been gaining much popularity, also claims to explain. An increasing number of scholars have adopted the concept for analysing transformations of communication not only in the political realm, but also in the judiciary (Peleg and Bogoch, 2012), science (Peters et al, 2008), religion (Hjarvard, 2008a), sports (Nelson, 2010), and tourism (Jansson, 2002), and in society as a whole (Hjarvard, 2008b;Mazzoleni, 2008).…”
Section: Notementioning
confidence: 99%